Effect of Supplementing Probiotic, Prebiotic and Synbiotic on Haematological Parameters in Weaned Gir Calves - Parmar, Monika R Parmar; Odedra, M D; Savsani, Harish H; Fefar, Dhaval T; Patbandha, Tapas. K; Gadariya, Mahesh R (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Good management practices to optimize nutrition, growth, immune status and decrease the risk of disease are vital in livestock. The use of probiotic, prebiotics and synbiotic may be a viable option to increase the proliferation of commensal bacteria in the gastrointestinal tract, modulate feeding behaviour, and optimize calf health. Twenty-four weaned Gir calves (4-6 month old) were distributed into four equal homogenous groups on the basis of their live body weight and sex in completely randomized design (CRD). The control (T1) group was offered a basal diet consisting of concentrate, green sorghum and dry fodder (Groundnut haulms) without any additional supplementation, while T2, T3 and T4 groups were supplemented basal diet with probiotic @ 10 gm/calf/day, prebiotic @ 10 gm/calf/ day, symbiotic @ 20 gm/calf/day, respectively, for a period of 180 days. The haematological parameters and blood glucose levels did not differ significantly among the groups and were within the normal physiological range throughout the experimental period. However, overall mean value of serum growth hormone (GH) was significantly higher in T4 followed by T1, T2 and T3 groups. Thus, it can be inferred that, probiotic, prebiotic and symbiotic should be added in the diets of weaned Gir calves to maximize overall performance and overall profit for well-being of farmers.